A Novel Approach for Space Vector Based PWM Algorithm for Diode Clamped Three level VSI Fed Induction Motor Drive - Debanjan Roy; Madhu Singh; Tapas Roy (Institute of Advanced Engineering and Science, 2017)
Performance of a voltage source inverter depends on pulse width modulation algorithms. Various algorithms exist for conventional space vector as well as space vector based bus clamped pulse width modulation for multilevel inverter in the literature. In this paper appropriate region selection algorithm for conventional space vector pulse width modulation (CSVPWM) and bus clamped pulse width modulation (BCPWM) techniques are proposed for diode clamped three level voltage source inverter. The proposed techniques are implemented on a three level voltage source inverter fed induction motor drive for open loop operation. The schemes are simulated in MATLAB/SIMULINK environments. The merit of proposed region selection algorithm is tested and verified through simulation result. Further performance comparisons between SVPWM and BCPWM for different modulation index are discussed.